Health Education for Diabetes Medication Adherence via the Whatsapp Messaging App (WEDMA) Module: A Content Validity Study - Alif Ramli; Fredie Robinson (Universiti Putra Malaysia, 2023)
Introduction: Medication non-adherence is still a substantial setback to better health outcomes for diabetic patients. Based on Health Belief Model (HBM) a practical health education module using WhatsApp messaging app called WEDMA was developed where the focus is on diabetes medication adherence among uncontrolled type II diabetes patients in Malaysia. This study aimed to examine the validity of the module content utilizing a systematic approach. Methods: The module for health education on diabetes medication adherence among uncontrolled type II diabetes patients consisted of 12 domains was systematically validated by a panel of experts for content validation in six consecutive steps. The proportion of experts who gave a rating of 3 or 4 was used to calculate the item content validity index (I-CVI). The I-CVIs were averaged to create the scale content validity index (S-CVI/Ave) and scale content validity index based on the universal agreement (S-CVI/UA) was used as a tool evaluate the module. Results: For all 36 items of the 12 domains of the WEDMA module, the I-CVIs ranged between 0.86 and 1.0, indicating an acceptable content validity. The S-CVI/Ave scored 0.98 and the S-CVI/UA scored 0.83 met acceptable values. Conclusion: The content validating study indicated that the newly developed WEDMA module is acceptable good module to be implemented for HBM based WhatsApp messaging app health education intervention to improve diabetes medication adherence in practical diabetes self-management.